2014
DOI: 10.1002/jcph.404
|View full text |Cite
|
Sign up to set email alerts
|

Ascending-dose study of noribogaine in healthy volunteers: Pharmacokinetics, pharmacodynamics, safety, and tolerability

Abstract: Noribogaine is the active metabolite of the naturally occurring psychoactive substance ibogaine, and may help suppress withdrawal symptoms in opioid-dependent subjects. The objectives of this Phase I study were to assess the safety, tolerability, pharmacokinetic, and pharmacodynamic profiles of noribogaine. In this ascending single-dose, placebo-controlled, randomized, double-blind, parallel-group study in 36 healthy drug-free male volunteers, 4 cohorts (n = 9) received oral doses of 3, 10, 30, or 60 mg or mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 14 publications
1
51
3
1
Order By: Relevance
“…The slightly higher logP for ibogaine compared to noribogaine indicates that ibogaine is slightly more lipophilic than noribogaine. We found a much higher half-life of noribogaine in our patient than the authors of a dose-ascending study investigating the PK/PD in healthy volunteers: 2540 h vs. 28-49 h [9]. However, the toxicokinetic parameters in our patient revealed a much higher C max , which may account for the difference in these evaluated parameters.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…The slightly higher logP for ibogaine compared to noribogaine indicates that ibogaine is slightly more lipophilic than noribogaine. We found a much higher half-life of noribogaine in our patient than the authors of a dose-ascending study investigating the PK/PD in healthy volunteers: 2540 h vs. 28-49 h [9]. However, the toxicokinetic parameters in our patient revealed a much higher C max , which may account for the difference in these evaluated parameters.…”
Section: Discussioncontrasting
confidence: 75%
“…However, the toxicokinetic parameters in our patient revealed a much higher C max , which may account for the difference in these evaluated parameters. In literature, due to fluctuations in individual distribution-phase concentration-time profiles, the presence of enterohepatic recirculation for noribogaine was suggested as a factor for prolonged elimination [9]. In our patient, we measured fluctuating noribogaine plasma-concentrations.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The use of higher doses (eg, ∼500–800 mg or higher, which might be used for treatment of opioid withdrawal or craving) was not considered acceptable, because of the population being tested (healthy volunteers), likely hallucinatory effects, and unknown ECG safety profile. An earlier noribogaine pharmacokinetic study indicated acceptable assay sensitivity around this dose range.…”
mentioning
confidence: 86%
“…2 To date, ibogaine has not been evaluated in randomized controlled trials. 5 The objectives of the present study were to evaluate the safety and tolerability, pharmacokinetics, and pharmacodynamics of single-dose noribogaine in patients seeking to discontinue methadone opioid substitution treatment (OST). Subsequent research has identified ibogaine as being rapidly converted oxidatively to an active metabolite, noribogaine, 3 which is eliminated much more slowly than ibogaine and thus might contribute to its antiwithdrawal and anticraving effects.…”
mentioning
confidence: 99%